PENGARUH SIARAN PERS PT. NIPPON INDOSARI CORPINDO TBK. PASCA AKSI 212 TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN SARI ROTI (STUDI PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS TELKOM UNIVERSITY) - Tino Dhamroni; Muhammad Sufyan Abdurrahman (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2017)
This research uses quantitative research method with descriptive and associative research type using causal relation. Sampling technique used was nonprobability sampling technique. Technique taken from nonprobability sampling was purposive sampling technique and incidental sampling technique with number of sample counted 100 respondents. Data analysis technique used was descriptive analysis and simple linear regression analysis. Based on the results of partial hypothesis testing (t-test), obtained from PT. Nippon Indosari Corpindo Tbk. press release has a significant influence on purchase decision of Sari Roti among students of School of Economics and Business Telkom University. This is proofed by the results t-count> t-table (7.438> 1.984). Then, based on the results determined, obtained press release PT. Nippon Indosari Corpindo Tbk was able to explain consumer's purchase decision of 36.1%, while the rest equal to 63.9% by other factors not examined in this research such as brand image, and promotion in television media. The conclusion of this research is press release PT. Nippon Indosari Corpindo Tbk and consumer purchase decision of Sari Roti have entered into good category. Then, the influence of PT. Nippon Indosari Corpindo Tbk Press Release on consumer purchase decision of Sari Roti is already significantly.